2021
DOI: 10.2147/cmar.s333823
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Clinical Outcomes with Posttreatment Changes in the Relative Eosinophil Counts and Neutrophil-to-Eosinophil Ratio in Patients with Advanced Urothelial Carcinoma Treated with Pembrolizumab

Abstract: Background To evaluate the association of clinical outcomes with posttreatment changes in the relative eosinophil count (REC) and neutrophil-to-eosinophil ratio (NER) in patients with advanced urothelial cancer (UC) treated with pembrolizumab. Materials and Methods We retrospectively analyzed 105 patients with advanced UC who received pembrolizumab after the failure of platinum-based chemotherapy. The REC and NER before and three weeks after pembrolizumab were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“… 37 Furthermore, we recently reported that an increased REC after pembrolizumab treatment was associated with superior OS in comparison to a decreased REC in advanced UC patients who received pembrolizumab therapy. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 37 Furthermore, we recently reported that an increased REC after pembrolizumab treatment was associated with superior OS in comparison to a decreased REC in advanced UC patients who received pembrolizumab therapy. 17 …”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 Furthermore, a number of clinical biomarkers of the response to ICIs have been reported for advanced UC, 13–16 and we previously reported that an increased relative eosinophil count (REC) after three weeks of pembrolizumab treatment may be associated with improved clinical outcomes. 17 However, it is still unclear whether an increased REC would cause increased numbers of irAEs or specific irAEs.…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the increase in REC and decrease in NER after pembrolizumab were associated with improved OS. 13 Therefore, the absence of eosinophil changes (eg, increase of REC and decrease of NER) may have also contributed to the shorter OS in the PS ≥2 group in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…Similarly, patients with a poor PS are unlikely to be incorporated in clinical trials considering the safety profile. Recently, eosinophils have been highlighted as potential biomarkers and have been studied in patients with advanced UC treated with ICIs; 12 , 13 however, no studies have investigated eosinophils in older patients or patients with a poor PS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation